1997
DOI: 10.1021/ic9608612
|View full text |Cite
|
Sign up to set email alerts
|

Aryldiazene, Aryldiazenido, and Hydrazine Complexes of Manganese. Preparation, Characterization, and X-ray Crystal Structures of [Mn(CO)3(4-CH3C6H4NNH){PPh(OEt)2}2]BF4 and [Mn(CO)3(NH2NH2){PPh(OEt)2}2]BPh4 Derivatives

Abstract: Aryldiazene complexes [Mn(CO)(3)(ArN=NH)P(2)]BF(4) (1, 2) and [{Mn(CO)(3)P(2)}(2)(&mgr;-HN=NArArN=NH)](BF(4))(2) (3, 4) [P = PPh(OEt)(2), PPh(2)OEt; Ar = C(6)H(5), 2-CH(3)C(6)H(4), 4-CH(3)C(6)H(4), 4-CH(3)OC(6)H(4); ArAr = 4,4'-C(6)H(4)C(6)H(4), 4,4'-(2-CH(3))C(6)H(3)C(6)H(3)(2-CH(3)), 4,4'-C(6)H(4)CH(2)C(6)H(4)] were prepared by reacting hydride species MnH(CO)(3)P(2) with the appropriate aryldiazonium cations in CH(2)Cl(2) or acetone solutions at -80 degrees C. The compounds were characterized by IR, (1)H an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 58 publications
1
14
0
Order By: Relevance
“…[17] The use of a mixed-ligand phosphite-carbonyl Re(CO) n P 5Ϫn fragment allows new examples of the stabilization of monodentate diazene to be achieved. It should be noted that the re- 4 , [11] but give only thermally unstable diazene complexes, which cannot be isolated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] The use of a mixed-ligand phosphite-carbonyl Re(CO) n P 5Ϫn fragment allows new examples of the stabilization of monodentate diazene to be achieved. It should be noted that the re- 4 , [11] but give only thermally unstable diazene complexes, which cannot be isolated.…”
Section: Methodsmentioning
confidence: 99%
“…[5] Furthermore, rhenium complexes containing NH 2 NH 2 or substituted hydrazine RNHNH 2 are very rare and include, apart from the pioneering work on [Re(NCO)-(CO) 2 (NH 2 NH 2 )P 2 ] (P ϭ tertiary phosphane), [6] only two papers, [7,8] one on [ReCp*Me 3 (NH 2 NH 2 )]CF 3 SO 3 (Cp* ϭ pentamethylcyclopentadienyl) and [Re(NH 2 NH 2 )-(CO) 3 (PPh 3 ) 2 ]CF 3 SO 3 , and another on the substitutedhydrazine complex [ReCl 2 (PPh 3 ) 2 {NNC(O)Ph}{H 2 NNHC-(S)Ph}]. [9] We have previously reported the synthesis and reactivity of mono-and bis(hydrazine) complexes of the iron triad [10] and manganese [11] of the type [MH(RNHNH 2 )P 4 ]BPh 4 , [M(RNHNH 2 ) 2 P 4 ](BPh 4 ) 2 (M ϭ Fe, Ru, Os) and [Mn(RNHNH 2 )(CO) n P 5Ϫn ]BPh 4 (P ϭ phosphites). We have now extended these studies to rhenium with the aim of pre- (CH 3 NHNH 2 )(CO) n P 5−n ]BPh 4 (n = 1, 2) with Pb(OAc) 4 at −40°C gives both [Re(CH 3 N=NH)(CO) n P 5−n ]BPh 4 and [Re(η 1 -NH=CH 2 )(CO) n P 5−n ]BPh 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The signal at 195 ppm was for carbonyl carbons. Carbon atoms of phenolic C-OH groups signals were detected at about 130 and 129 ppm for A1 and A2 [8][9][10][11][12][13]35].…”
Section: Liquid Phase and Solid Phase Nmrmentioning
confidence: 99%
“…Diazonium cations are very important intermediates in the synthesis of derivatized organic and inorganic compounds because of their good electrophilic properties [3][4][5]. Even though many studies have been reported on the synthesis of mono(aryldiazonium) cations ArN þ 2 , synthesis of novel solid-supported bis(diazoimine) ligands and their solid phase extraction properties using syringe technique can be considered as a new area [6][7][8][9][10][11][12][13]. Silica-gel can be chemically activated with an active compound such as 3-aminopropyltriethoxysilane (APTES) before supporting chemicals to its surface [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In the search toward new metallic species with biological applications, copper compounds have proved to be excellent candidates [1][2][3][4][5][6][7]. The specific roles of ligands analogous to the molecules that bind to or modulate the function of biological receptors make them good candidates for drug development.…”
mentioning
confidence: 99%